Prediction of tongue obstruction observed from drug induced sleep computed tomography by cephalometric parameters. Issue 3 (June 2019) - Mittal, Rashu; Lee, Li-Ang; Lin, Cheng Hui; Hsin, Li-Jen; Bhusri, Navdeep; Li, Hsueh-Yu
Abstract: Objective: To elucidate potential role of cephalometric measurements to predict tongue base obstruction as observed on drug Induced Sleep Computed Tomography (DIS-CT). Methods: Study included 35 patients with moderate to severe sleep apnea who underwent DIS-CT & cephalometric examination to assess tongue base obstruction. Results: Statistically significant difference was noted for SNA angle & Mandibular posterior airway space (PAS) among groups with total tongue obstruction versus Non-total tongue obstruction identified on DIS-CT. Conclusion: Lateral cephalogram can be used as a standard screening tool with commonly used skeletal and soft tissue parameters to predict the possibility of tongue collapse/obstruction during sleep in patient with moderate to severe OSAS.